RELATIONSHIP MARKETING TERHADAP CUSTOMER RETENTION DAN CUSTOMER LOYALITY PADA NASABAH BANK MEGA, Tbk. MALANG - -, Zulkifli (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstract : Competition that is increasingly sharply this claims every bank that be able to maintain and takes care of the client loyality. One of strategy needed to by the thing is strategy Relationship Marketing. This research done to know influence Relationship Marketing to Retensi Pelanggan and Loyalitas cutomer. This research done to the clients by using sampling technique. Sample measure taken is 75. Data is collected by through interview by using questionaire and hereinafter processing data by using descriptive analysis and path analysis. Result of analysis indicates that Commitment, Trust and Relationsship Satisfaction influential signifikan to Customer Retention. This research also shows existence of influence signifikan between Customer Loyalty, there is influence signifikan between Trust directly and also indirectly through Customer Retention to Customer Loyalty while Commitment and Relationship Satisfaction doesn´t have an effect on to Customer Loyalty. Key words: Commitment, Trust, Relationship Satisfaction, Customer Retention and Customer Loyalty